CO observations toward the isolated mid-infrared bubble S44: External triggering of O-star formation by a cloud–cloud collision. (9th November 2018) - Kohno, Mikito; Tachihara, Kengo; Fujita, Shinji; Hattori, Yusuke; Torii, Kazufumi; Nishimura, Atsushi; Hanaoka, Misaki; Yoshiike, Satoshi; Enokiya, Rei; Hasegawa, Keisuke; Ohama, Akio; Sano, Hidetoshi; et al.
Abstract: We have performed a multi-wavelength study of the mid-infrared bubble S44 to investigate the origin of isolated high-mass star(s) and the star-formation process around the bubble formed by the H ii region. We report on the results of new CO observations ( 12 CO, 13 CO J = 1–0, and 12 CO J = 3–2) toward the isolated bubble S44 using the NANTEN2, Mopra, and ASTE radio telescopes. We found two velocity components at −84 km s −1 and −79 km s −1 in the direction of the bubble. These two clouds are likely to be physically associated with the bubble, because of the enhanced 12 CO J = 3–2/1–0 intensity ratio from a ring-like structure affected by ultraviolet radiation from embedded high-mass star(s) and of the morphological correspondence between the 8 μm emission and the CO distribution. Assuming a single object, we estimate a spectral type of the embedded star inside the bubble to be O8.5–9 $({\sim}20\, M_{\odot})$ from the radio-continuum free–free emission. We hypothesize that the two clouds collided with each other 3 Myr ago, triggering the formation of the isolated high-mass star in S44, as also occurred in RCW 120 and RCW 79. We argue that this scenario can explain the origin of the isolated O-star inside the bubble.